THE INDEPENDENCE OF THE REPUBLIC OF UZBEKISTAN. NATIONAL SYMOLS OF THE REPUBLIC OF UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This abstract explores the significance of national symbols in shaping the identity and unity of the Republic of Uzbekistan following its independence in 1991. It delves into the historical context surrounding Uzbekistan's break from the Soviet Union and the subsequent emergence of distinct national symbols—the flag, emblem, and anthem—that embody the nation's rich heritage and aspirations. By examining the meanings behind these symbols and their roles in education, cultural events, and international representation, this abstract highlights how they contribute to fostering a strong sense of pride and unity among Uzbekistan's citizens. Furthermore, it discusses ongoing efforts to preserve and promote these symbols as vital components of Uzbekistan's evolving identity in the global arena. Ultimately, this abstract emphasizes the enduring significance of national symbols in defining and celebrating the unique cultural identity of the Republic of Uzbekistan.